Peningkatan Keaktifan dan Hasil Belajar Matematika Melalui Penerapan Model Cooperative Learning Tipe Buzz Group - Elly Dwiana Hendrawati (Nur Science Institute, 2021)
This study aims to improve the activeness and learning outcomes of Mathematics through the application of the Buzz Group Type Cooperative Learning model in class IX H semester 2 students at SMP N 24 Surakarta in the 2017/2018 academic year. This classroom action research was conducted at SMP N 24 Surakarta in semester 2 of the year. 2017/2018 lessons for 3 months. The research subjects were 29 students of class IX H of SMP N 24 Surakarta. The method used in this research is a classroom action research method which is carried out in 3 cycles through 4 stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. In the implementation of classroom action research using observation sheets and learning outcomes tests. Data analysis used comparative descriptive analysis technique. The results of this classroom action research show that the application of the Buzz Group Type Cooperative Learning model can increase the activeness and learning outcomes of Mathematics in class IX H semester 2 students at SMP N 24 Surakarta in the 2017/2018 academic year.